Pro Hibernate and MongoDB - Leonard, Anghel (Apress Imprint: Apress, 2013)
Hibernate and MongoDB are a powerful combination of open source persistence and NoSQL technologies for today's Java-based enterprise and cloud application developers. Hibernate is the leading open source Java-based persistence, object relational management engine, recently repositioned as an object grid management engine.  MongoDB is a growing, popular open source NoSQL framework, especially popular among cloud application and big data developers.  With these two, enterprise and cloud developers have a "complete out of the box" solution.  Pro Hibernate and MongoDB shows you how to use and integrate Hibernate and MongoDB.  More specifically, this book guides you through the bootstrap; building transactions; handling queries and query entities; and mappings.  Then, this book explores the principles and techniques for taking these application principles to the cloud, using the OpenShift Platform as a Service (PaaS) and more.  In this book, you get two case studies: An enterprise application using Hibernate and MongoDB.  then, A cloud application (OpenShip) migrated from the enterprise application case study After reading or using this book, you come away with the experience from two case studies that give you possible frameworks or templates that you can apply to your own specific application or cloud application building context.